2021
DOI: 10.1088/1755-1315/786/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Revisited the matter of the fodder galega new feed crop cultivation on the irrigated lands of the Lower Volga region

Abstract: The research results carried out on light-chestnut soils in 2011-2017 are presented, in order to determine the rational parameters of the water, nutritional regimes of the soil and various varieties of fodder galega to create highly productive herbage with their long-term use. The study of the fertilizers calculated doses influence and various pre-irrigation soil moisture thresholds on the herbage density showed that the maximum number of shoots was formed in the Magistr variety crops while maintaining an 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that the supply of productive moisture in the soil depended on its type, methods of cultivation, the depth of cultivation, and the time of its implementation (de Lima et al, 2021;Mesterházy et al, 2020). According to Burtseva et al (2021), on light chestnut soils of the Lower Volga region, the most favorable water regime is formed with non-moldboard tillage with subsurface cultivators and SibIME stands while maintaining the maximum amount of stubble, which contributes to the complete assimilation of precipitation. Due to the deterioration of the water regime, shallow soil cultivation can be used in combination with periodic deep or other methods of decompaction of the lower soil layers, primarily in years with its low autumn moisture load.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the supply of productive moisture in the soil depended on its type, methods of cultivation, the depth of cultivation, and the time of its implementation (de Lima et al, 2021;Mesterházy et al, 2020). According to Burtseva et al (2021), on light chestnut soils of the Lower Volga region, the most favorable water regime is formed with non-moldboard tillage with subsurface cultivators and SibIME stands while maintaining the maximum amount of stubble, which contributes to the complete assimilation of precipitation. Due to the deterioration of the water regime, shallow soil cultivation can be used in combination with periodic deep or other methods of decompaction of the lower soil layers, primarily in years with its low autumn moisture load.…”
Section: Introductionmentioning
confidence: 99%